Analisis Komponen Pertumbuhan Ekonomi Di Kabupaten Probolinggo - Zalza Nur Sabila; Misbahul Farisiyah; Siti Maisyaroh (PT. Saha Kreasi Indonesia, 2026)
This study aims to analyze the structure of economic growth in Probolinggo Regency by identifying basic and non-basic sectors, and to evaluate the role of leading sectors in driving sustainable regional development. Using a descriptive qualitative approach, data were collected through in-depth interviews with informants from the Regional Development Planning Agency (Bappeda) and economic actors, field observations, and analysis of GRDP documents. The results indicate that the agricultural sector remains the backbone (basic sector) of the regional economy, providing a multiplier effect for other sectors. Furthermore, Small and Medium Industries (SMEs) based on natural product processing are beginning to demonstrate a significant role in creating added value. These findings validate the Economic Base Theory, which states that strengthening basic sectors is crucial for stimulating growth in non-basic sectors (trade and services). The study concludes that synergy between government policies and local potential (particularly MSMEs) is key to inclusive development. A recommendation for future research is the use of mixed methods to more precisely quantify sector competitiveness.